Clinical ethics consultation in neurology: a case series - Ilse, Benjamin; Alt-Epping, Bernd; Günther, Albrecht; Liman, Jan; Simon, Alfred (BMC neurology, 2021)
The concept of clinical ethics consultation (CECs) was implemented to provide support in ethical controversies in clinical settings and are offered in at least every second hospital in Germany. Neurological disorders often require complex decision-making. The aims of this study were to determine which situations lead to CEC in neurology and to investigate the influence of the individual patient’s wishes on the recommendation.
Gesehen am 29.07.2021